+0

# For x = (-2)^-3 solve this : A = (x - 2)*(x+5) - (x - 4)*(x + 3) + 4x

0
510
4
+65

For x = (-2)^-3  solve this : A = (x - 2)*(x+5) - (x - 4)*(x + 3) + 4x

I just cannot find a way to solve this, so please if anyone actually helps can you  show how you solved it?

Sep 23, 2015

#2
+107156
+10

For x = (-2)^-3  solve this : A = (x - 2)*(x+5) - (x - 4)*(x + 3) + 4x

x = (-2)^(-3)   = 1 / (-2)^3   = -1/8     so we have

A = [ (-1/8) - 2] [ (-1/8) + 5 ] - [ (-1/8) - 4 ] [(-1/8) + 3] + 4 [ -1/8 ]

A  = [ -17/8] [39/8] - [ -33/8][ 23/8] - 1/2

A = [ -663 / 64] + [759/64] - 32/64

A = [ 759 - 663 -  32 ] / 64

A = 64 / 64

A = 1

Sep 23, 2015

#1
+5

The result of all those expressions=1

Sep 23, 2015
#2
+107156
+10

For x = (-2)^-3  solve this : A = (x - 2)*(x+5) - (x - 4)*(x + 3) + 4x

x = (-2)^(-3)   = 1 / (-2)^3   = -1/8     so we have

A = [ (-1/8) - 2] [ (-1/8) + 5 ] - [ (-1/8) - 4 ] [(-1/8) + 3] + 4 [ -1/8 ]

A  = [ -17/8] [39/8] - [ -33/8][ 23/8] - 1/2

A = [ -663 / 64] + [759/64] - 32/64

A = [ 759 - 663 -  32 ] / 64

A = 64 / 64

A = 1

CPhill Sep 23, 2015
#3
+65
+1

Thanks alot!

Sep 23, 2015
#4
+107156
+5

No prob, Lunar.......

Sep 23, 2015